Knowledge Virtualization and Local Connectedness among Smart High-tech Companies - Marina van Geenhuizen; Peter Nijkamp (Tinbergen Institute, 2011)
Smart high-tech companies are characterized by knowledge intensity and open innovation. Even when these companies emerge in spatial clusters or dense urban places, they may utilize knowledge networks on a global scale. However, there is not much insight into the factors that shape knowledge networks, the role of virtualization herein and the impact of on global knowledge sourcing on local connectedness. This paper seeks to fill these gaps in understanding, by drawing on a selected sample of young high-technology companies in the Netherlands and application of rough set analysis to identify homogeneous categories of companies in the highly differentiated segment of young high-tech companies. The outcomes suggest that employing mainly local and employing mainly global knowledge networks coexist in city-regions, and that only part of the globalized companies are losing local connectedness, particularly those involved in co-creation with global customers and those acting as learning partners of multinational corporations ('reverse' knowledge transfer). Factors counteracting a weakening of local connectedness are specific local knowledge relationships and the strategy of developing local/regional customer markets.
urn:NBN:nl:ui:31-1871/38528
Keywords: O14; D21; 330; high-technology companies; open innovation; knowledge networks; strategic focus; dynamic capabilities; virtualization; local connectedness; rough set analysis; Innovationsmanagement; Virtuelle Realität; Unternehmensnetzwerk; Regionales Cluster; Hochtechnologie; Niederlande